Molecular detection of metallo-β-lactamase genes, bla(IMP-1), bla(VIM-2) and bla(SPM-1) in imipenem resistant Pseudomonas aeruginosa isolated from clinical specimens in teaching hospitals of Ahvaz, Iran - Moosavian, Mojtaba (Iran J Microbiol, 2015)
BACKGROUND AND OBJECTIVES: Carbapenem resistant Pseudomonas aeruginosa is a serious cause of nosocomial infections. The main purpose of the study is to determine the prevalence rate of imipenem resistant Pseudomonas aeruginosa carrying metallo-ß-lactamase (MBL) genes. MATERIAL AND METHODS: 236 Pseudomonas aeruginosa isolates were collected from teaching hospitals of Ahvaz University of Medical Sciences during a period of 9 months in 2012. These strains were identified using conventional microbiological tests. The susceptibility of isolates to antibiotics were assessed using disk diffusion test. The IMP-EDTA combination disk phenotypic test was performed for detection of MBL producing strains. Finally, polymerase chain reaction (PCR) was performed to detect MBL genes, bla(IMP-1), bla(VIM-2) and bla(SPM-1) in imipenem resistant strains. RESULTS: Out of 236 examined isolates, 122 isolates (51.4%) were resistant to imipenem. The IMP-EDTA combination test showed that among 122 imipenem resistant strains, 110 strains (90%) were phenotipically MBL producers. Additionally, the results of PCR method showed that 2 strains (1.6%) and 67strains (55%) of imipenem resistant Pseudomonas aeruginosa isolates contained bla(VIM-2) and bla(IMP-1) genes respectively. No SPM-1gene was found in the examined samples. CONCLUSION: Resistance of P. aeruginosa isolates to imipenem due to MBL enzymes is increasing in Ahavaz. Because of clinical significance of this kind of resistance, rapid detection of MBL producing strains and followed by appropriate treatment is necessary to prevent the spreading of these organisms.